Pengawasan Pendistribusian Gas LPG 3 Kg Bersubsidi Di Kota Batam - Sri Ratna Dewi; Nurlaily; Triana Dewi Seroja (Jurnal Ilmiah Penegakan Hukum, 2023)
The purpose of this research is to find ou the supervision carried out by the industry and trade service (disperindag) of batam city in supervising the circulation of subsidized lpg to be right on target and create justice in society especially people in the Sungai Harapan, Sekupang, Batam. Based on the rules contained in mineral resources regulation No 26 of 2009 concerning the supply and distribution of 3 Kilogram of LPG. Where user of 3 kilogram LPG consist of households and small, micro, and medium enterprises (ESDM). Housheld are families with low economic class, namely families with income below Rp 1,500,000 ,- ( one million five hundred thousand rupiah) and is in the distribution area of subsidized kilogram LPG. The research metho used in weiting is descriptive qualitative research, the source of information obtained from the staff (Disprindag) of Batam in charge of supervision and activities related to energy and natural resources (ESDM). Data collection methods used by the autjor in this study sre observation, interviews and data analysis. Research results the results show that the department of industry and trade has not optimally carried out supervision where vio;ations are still found in the distribution o subsidized LPG such as sa;es that are not on target so that subsidized LPG can be used by anyone. Therefore the cooperation of various parties, especially the department of industry and trade with the community mus be increased sothat irregularities do not occur in the distribution of subsidized LPG which in society